The role of renal dual-energy computed tomography in exploring the gouty kidney: the RENODECT study - Tristan Pascart; Elie Dauphin; Chio Yokose; Charlotte Jauffret; Aurore Pacaud; Victor Laurent; Vincent Ducoulombier; Hyon K. Choi; Jean-François Budzik (Annals of Medicine)
Objective The objective of this study was to explore the ability of dual-energy computed tomography (DECT) to detect monosodium urate (MSU) crystal deposits in the kidneys and renal artery walls, and uric acid urolithiasis, in patients with gout and chronic kidney disease (CKD).Methods Patients with gout and with stage 2–4 CKD were prospectively included in this cross-sectional study. Patients underwent renal, knee and feet DECT scans. Renal DECT scans were read for MSU-coded lesions in the kidneys, renal artery walls, and urinary tract using different post-processing settings. Characteristics of patients with and without DECT-positive lesions were compared, and the DECT parameters of these lesions were measured.Results A total of 27/31 patients with had renal DECT scans and were included in the analysis (23/27 men, mean (standard deviation) 73 (9) years old, mean eGFR 45.3 mL/min/1.73 m2 (21.0), volumes of MSU in the knees and feet ranging from 0.11 to 475.0 cm3). None of the patients exhibited deposition of MSU crystals in the kidneys. One case of calyceal calculi and one case of ureterolithiasis were observed, wrongly coded as MSU in default post-processing settings for gout but identified as uric acid in the “kidney stone” settings. Five patients had MSU-coded plaques in the renal arteries, which had DECT parameters consistent with early calcified plaques rather than MSU, and had no association with volumes of peripheral MSU deposition.Conclusion DECT is unable to detect genuine monosodium urate crystal deposits in kidneys and renal artery walls, and but can characterize chronic asymptomatic urolithiasis.